The impact of wind power support schemes on technology choices - Nils May (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Germany changed renewable remuneration for wind power from a fixed Feed-In Tariff (FIT) to a floating Market Premium Scheme (MPS) in 2012. One aim of this adjustment was to better align the supply of generated wind electricity with the demand for it, e.g. through more system-friendly wind turbine technology choices. In energy systems with a high share of variable renewable energies, such turbines produce a higher share of their production at lower wind speeds and thus can reduce the need for alternative flexibility options like back-up capacity, storage, grid extensions and demand side measures. However, based on a wind power investment model, I show that the MPS fails to convey strong enough incentives to project developers to significantly alter their investment decisions as long as these base their investments on current electricity market price profiles and are limited by their access to risk-averse project finance. One reform proposal to support the installation of system-friendly turbines is a change in the production volume-based benchmark approach which plays an integral part in both the fixed FIT and the MPS. The investment model indicates that such a revised policy can incentivize the deployment of moderately more system-friendly wind power technologies at some locations. An alternative option is to shift to a production value-based benchmark approach. It directly reflects the future additional market value of system-friendly turbines in today's remuneration structure. Thus, this approach sets incentives also for investors without perfect foresight - or with financing constraints - to deploy more systemfriendly turbines that meet the requirements of power systems with increasing shares of wind power.
Keywords: Q42; Q55; O38; 330; Renewable Energies; Wind Power Technology; Feed-in Tariff; Project Finance; Market Premium